Concanavalin A induced suppressor cell activity and autorosette forming cells in chronic myeloid leukemia patients. - Somasundaram, R. (Nature Publishing Group, 1983)
In the present paper attempts have been made to investigate suppressor cell activity in CML patients in first and subsequent remissions in order to study the relationship between suppressor cell activity and progression of the disease. For this purpose, the ability of Con A activated suppressor cells from peripheral blood of CML patients in 1st, 2nd and 3rd remission to suppress PHA response of autologous lymphocytes is investigated and compared with that of normal healthy donors. The ability of Con A activated cell population to form rosettes with autologous RBCs (ARFC) is also investigated. The results indicate that lymphocytes from CML patients in 1st (61.8 +/- 6.1%), 2nd (62.6 +/- 3.0%) and 3rd (55.3 +/- 4.8%) remissions show significantly high suppressor cell activity than normal healthy donors (36.5 +/- 1.9%) when activated with Con A. Similarly, generation of spontaneous suppressor cell activity was also higher in 1st (23.3 +/- 4.7%) and 2nd (25.3 +/- 4.2%) remission lymphocytes than controls (10.1 +/- 2.5%). In the 3rd remission however, the spontaneous suppressor cell activity (14.5 +/- 3.2%) was comparable to controls. Thus it appears that a higher suppressor cell precursor population is present in CML patients in remission. However, this could not be correlated with the progression of the disease. CML patients in 1st remission also revealed an increased percentage of ARFC which correlated with the suppressor cell function. The ARFC activity tested in a few patients in subsequent remissions was comparable with controls although functional suppressor activity was increased.